Performance of LED with mixed wavelengths or two-phase culture on the growth and lipid accumulation of Chlorella pyrenoidosa - Chu, Bingquan; Zhao, Jiewei; Zheng, Huimin; Gong, Jinyan; Chen, Kai; Zhang, Suwan; Xiao, Gongnian; He, Yong (International Journal of Agricultural and Biological Engineering, 2021)
Chlorella pyrenoidosa, a type of lipid-rich green algae, features broad prospects for application in such fields as healthy foods, biodiesel and so on. The light-utilizing efficiency of the cells is a critical factor that influences the biomass and lipid contents of photoautotrophic microalgae. Inconsistent illumination wavelengths hinder microalgal growth. The patterns about the impacts of mixed light emitting diode (LED) wavelengths or two-phase culture over the growth and lipid accumulation of Chlorella pyrenoidosa were reported. Among the different LED wavelengths (white, purple, blue, green, yellow and red) at the light intensity of 200 μmol/m2·s tested, red and green gave maximum biomass and lipid contents, respectively. Based on the discovery, two-phase (red was illuminated for 12 d in the first phase, and then shifted to green light for 8 d in the second phase, R→G) or mixed LED (R:G=3:7 or R:G=7:3) culture protocol was adopted for the high lipid-accumulation of Chlorella pyrenoidosa. The results indicated that the lipid contents of Chlorella pyrenoidosa treated with two-phase (R→G) or mixed LED culture was significantly higher than that of white light with the same intensity (p<0.05), and the highest lipid-accumulation rate was 26.37 mg/L·d in the two-phase culture. Fatty acid (FA) analysis showed that 13 types FAs were detected and unsaturated FAs were over 50% (w/w). 26.8%-27.7% (w/w) palmitic acid (C16:0) was the major saturated FA, while the largest proportions of monounsaturated FA and polyunsaturated FA were oleic acid (C18:1) and linoleic acid (C18:2), respectively. Additionally, although no difference in the FA composition of Chlorella pyrenoidosa treated with different protocols was found, the absolute content did differ significantly, coinciding with that of the total lipids. Furthermore, the ratio of unsaturated FAs in Chlorella pyrenoidosa was significantly increased under the mixed LED (R:G=7:3) (p<0.05). Keywords: Chlorella pyrenoidosa, mixed LED wavelength, two-phase, biomass, lipid, fatty acid DOI: 10.25165/j.ijabe.20211401.6098 Citation: Chu B Q, Zhao J W, Zheng H M, Gong J Y, Chen K, Zhang S W, et al. Performance of LED with mixed wavelengths or two-phase culture on the growth and lipid accumulation of Chlorella pyrenoidosa. Int J Agric & Biol Eng, 2021; 14(1): 90–96.